User access control and security model - Crysdian, Cahyo; Selamat, Harihodin; Md. Sap, Mohd. Noor (Penerbit UTM Press, 2000)
Securing information system becomes the highlight of technology following quick development of computer networking and the Internet. People have known the method to enforce security over a database, but the necessities to get more secure system never reach boundaries. Now days the trend of information system is the open connection system where users are able to access system from many places. It leads the involvement of user access control as a part of database security since it takes a big role in governing access request of each user. This security component serves as a part of defense to secure data contained in the system. Development of user access control began on the early of seventies with DAC technology. Right now technology of user access control has reached sophisticated method with RBAC, but development of organization using information system and the development of information system itself push the improvement of user access control technology. This paper provides information about security system with the emphasis on user access control, which includes DAC, MAC and RBAC and the implementation of each user access control in security model. Comparison of each user access control method is given at the end of the paper.